Métissage et genre de la nation dans la presse de guerre paraguayenne - Luc Capdevila (Nuevo mundo - Mundos Nuevos, 2008)
This article aims to discuss the gender of paraguayan nation through the movilization call and pictures published in newspapers during the Triple Alianza war. The analysis point out to the fact that, by this way of representing the conflict, gender of Paraguayan nation was more and more marked ethnically speaking. On the other part, the representation of enemies wasn’t but a very established one, focused on ethnic desorder and sex desorder as well.